2019
DOI: 10.1002/ps.5448
|View full text |Cite
|
Sign up to set email alerts
|

Assessing crop damage from dicamba on non‐dicamba‐tolerant soybean by hyperspectral imaging through machine learning

Abstract: BACKGROUND Dicamba effectively controls several broadleaf weeds. The off‐target drift of dicamba spray or vapor drift can cause severe injury to susceptible crops, including non‐dicamba‐tolerant crops. In a field experiment, advanced hyperspectral imaging (HSI) was used to study the spectral response of soybean plants to different dicamba rates, and appropriate spectral features and models for assessing the crop damage from dicamba were developed. RESULTS In an experiment with six different dicamba rates, an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
(62 reference statements)
2
31
0
1
Order By: Relevance
“…Because this study is unique in this regard, there is a lack of literature to compare with. Still, the accuracy found here is similar to or even higher than those obtained by modeling different stresses effects in plants [21,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Because this study is unique in this regard, there is a lack of literature to compare with. Still, the accuracy found here is similar to or even higher than those obtained by modeling different stresses effects in plants [21,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 77%
“…Recently, machine learning approaches have been used in modeling the hyperspectral response of different conditions associated with vegetation [21]. The popular techniques used for analyzing data include regression analysis, vegetation indices, linear polarizations, wavelet-based filtering, and, currently, machine learning algorithms like random forest, decision tree, support vector machine (SVM), k-nearest neighbor (kNN), artificial neural networks (ANN), naïve Bayes (NB), and others [22][23][24][25]. To evaluate the hyperspectral response of plants, machine learning has already been implemented in different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the proposed system could utilize any one of the algorithms for the task of identifying lesions on cotton leaves [ 51 ]. However, the performance is far from ideal, since Mohanty et al [ 52 ] obtained a figure of 99.35% for accuracy in the detection of leaf diseases; Brahimi et al [ 53 ] found a figure of 99.18% for tomato leaves, and Zhang et al [ 54 ], an overall accuracy greater than 90% in the identification of damage to soybeans tolerant to the herbicide dicamba. All of these values are substantially superior to those obtained here.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, 2,4-dichlorophenoxyacetic acid (2,4-D) is one of the most used herbicides to control broadleaf weeds in agriculture; however, they often damage the neighboring 2,4-D sensitive cotton field resulting in the loss of millions of dollars in the USA and Australia [23]. Likewise, severe crop injury has been reported due to the off-target movement of dicamba to the neighboring fields with non-dicamba tolerant crops [24,25]. Further, increasing use of herbicides has led to the accumulation of agricultural contaminants like arsenic, cadmium, lead, and mercury in soil and water resources [26].…”
Section: Introductionmentioning
confidence: 99%